2015
DOI: 10.1371/journal.pone.0129082
|View full text |Cite
|
Sign up to set email alerts
|

Serum Total Cholinesterase Activity on Admission Is Associated with Disease Severity and Outcome in Patients with Traumatic Brain Injury

Abstract: BackgroundTraumatic brain injury (TBI) is one of the leading causes of neurological disability. In this retrospective study, serum total cholinesterase (ChE) activities were analyzed in 188 patients for diagnostic as well as predictive values for mortality.Methods and FindingsWithin 72 hours after injury, serum ChE activities including both acetylcholinesterase and butyrylcholinesterase were measured. Disease severity was evaluated with Acute Physiology and Chronic Health Evaluation (APACHE) II score, Glasgow … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 63 publications
3
14
0
Order By: Relevance
“…In conclusion, BChE activity can be regarded as a biomarker in PD, especially in PD-related dementia. The same function has also been reported in other disorders, including Alzheimer's disease [ 11 ], vascular dementia [ 25 ], ischemic stroke [ 26 ], traumatic brain injury [ 7 ], postoperative delirium [ 27 ], severe trauma [ 28 ], septic shock [ 29 ], burn injuries [ 30 ], adverse cardiac events [ 16 ], hepatic disease [ 17 ], diabetes [ 31 ], and hyperlipidemia [ 32 ]. A former study on AChE levels in PD patients suggested that polymorphisms in ACHE genes fail to initiate ACHE expression, resulting in an impaired Ach/DA balance and subsequent vulnerability of dopaminergic neurons and PD development [ 9 ].…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…In conclusion, BChE activity can be regarded as a biomarker in PD, especially in PD-related dementia. The same function has also been reported in other disorders, including Alzheimer's disease [ 11 ], vascular dementia [ 25 ], ischemic stroke [ 26 ], traumatic brain injury [ 7 ], postoperative delirium [ 27 ], severe trauma [ 28 ], septic shock [ 29 ], burn injuries [ 30 ], adverse cardiac events [ 16 ], hepatic disease [ 17 ], diabetes [ 31 ], and hyperlipidemia [ 32 ]. A former study on AChE levels in PD patients suggested that polymorphisms in ACHE genes fail to initiate ACHE expression, resulting in an impaired Ach/DA balance and subsequent vulnerability of dopaminergic neurons and PD development [ 9 ].…”
Section: Discussionsupporting
confidence: 57%
“…It is a key contributor to stress and enhances neuronal excitability. In addition, it also potently modulates the classical immune response by activating α 7 nicotinic Ach receptor on the surface of leukocytes in the so-called “cholinergic anti-inflammatory response” [ 7 ]. The cholinergic system is involved in many physiological functions of the central nervous system, and Ach can be hydrolyzed by acetylcholinesterase (AChE) and butyrylcholinesterase (BChE), two independent enzymes in the circulation system.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dysfunction of the CAP is also commonly complicated in severe septic condition, as evidenced by a massive loss of brain cholinergic neurons and vagal tone together with disturbed responses of Ach-α7nAchR machinery, which fails at inhibiting inflammation and protecting organs [14,112,113]. A close relationship has been noted between poor outcomes and indicators of CAP malfunction, such as a decrease in heart rate variability, an increase in cholinesterase activity, and downregulation of α7nAchR mRNA expression in peripheral immune cells [113][114][115]. Manipulation of CAP activity through stimulating brain cholinergic nuclei or vagus nerve, inhibiting cholinesterase activity and administering agonists of α7nAchR, is beneficial for organ function and survival of septic animals by reconstruction or simulation of CAP effects [9,10,116,117].…”
Section: Cholinergic Anti-inflammatory Pathwaymentioning
confidence: 99%
“…Due to the retrospective design of this current study, the PCIS data can only be presented with a translated supplementary table as a reference. Cholinesterase has been reported as a prognostic or severity marker for several diseases, including severe injury, 21 sepsis, 22 dementia, 23 and acute organophosphate pesticide poisoning. 24 LDH and a-HBDH levels are associated with renal damage and infection.…”
Section: Discussionmentioning
confidence: 99%